Comparative Assessment of Physical and Chemical Characteristics of Prickly Pear Seed Oil from Opuntia ficus-indica and Opuntia megacantha Varieties - Fatima Ettalibi; Abderraouf El Antari; Allal Hamouda; Chemseddoha Gadhi; Hasnaâ Harrak (Journal of Food Quality)
The prickly pear (Opuntia spp.) is an important plant in the economies of arid and semiarid areas, considering its low agronomic requirements and high water use efficiency. Characterizing the chemical composition of this plant will open new avenues for food, pharmaceutical, and cosmetic applications. In this context, this study examined the physical and chemical parameters of fruit seed oils of two prickly pear species from Rhamna area located in the center of Morocco: Opuntia ficus-indica (OFI), represented by the varieties “Safra” and “Aakria,” and Opuntia megacantha (OM), represented by the variety “Derbana.” The evaluated parameters included oil content, free acidity, specific extinction coefficients (K232 and K270), pigment content, fatty acid, and triglyceride composition. The seed oil contents of the three varieties “Safra,” “Aakria,” and “Derbana” were 8.09%, 8.74%, and 8.04%, respectively. OM (“Derbana”) seed oil was the most stable. The three studied varieties had higher contents of α-pheophytin and carotenoids than that of chlorophyll. Oil from the “Aakria” variety was distinguished by having the highest contents of α-pheophytin and chlorophyll. Significant differences in some fatty acid and triglyceride contents were noted. The major fatty acids of the three varieties were linoleic acid (60.55%–63.46%), followed by oleic acid (18.88%–21.81%) and palmitic acid (13.03%–13.75%). Furthermore, the chromatographic profiles of the triglycerides have shown the dominance of trilinolein (LLL, 24.33%–26.49%) and oleoyl-dilinoleoyl-glycerol (OLL, 20.92%–21.92%). Some triglycerides could be considered species markers, especially OLL, dipalmitoyl-linoleoyl-glycerol (PPL), oleoyl-linoleoyl-linolenoyl-glycerol and palmitoyl-oleoyl-dilinoleoyl-glycerol fraction (OLLn + PoLL), and stearoyl-dioleoyl-glycerol (SOO). This study provides a basis for qualitatively evaluating the therapeutic and cosmetic potential of prickly pear derivatives and for establishing quality standards of seed oil derived from the two species studied.